Potret Pekerja Miskin di Provinsi Jambi 2023 - Renaldi, Egi; Sari, Novalianisa Permata (Seminar Nasional Official Statistics, 2025)
Poverty is a global issue faced not only by Indonesia but also by many other developing countries. Poverty alleviation has become a top priority in the sustainable development agenda, one of which is through job creation. Employment availability is considered a crucial factor in driving economic and social development. However, the relationship between employment and poverty is not always linear. This is evident in Jambi Province, where the poverty rate is higher than the open unemployment rate (OUR). This study focuses on analyzing the factors that influence the poverty status of workers in Jambi Province. The data used in this study is secondary data sourced from the 2023 National Socio-Economic Survey (SUSENAS). Using Firth logistic regression, the results show that the number of household members, marital status, age, education level, area of residence, and number of working hours significantly affect the poverty status of workers.